Assessing the efficacy and experience of in-person versus telephonic psychiatric evaluations for asylum seekers in the U.S. (December 2019) - Bayne, Mitchell; Sokoloff, Lara; Rinehart, Rebecca; Epie, Axel; Hirt, Leeza; Katz, Craig
Highlights: Psychiatric evaluations are critical to refugees in the US seeking asylum. Affidavits from telephonic and in-person evaluations are of equivalent quality. Providers have positive attitudes towards telephonic evaluation of asylum seekers. Abstract: Psychiatric evaluations of asylum seekers in the U.S. play an important role in asylum cases; however, there are significant barriers to assessing asylum seekers' psychological trauma. Telephonic psychiatric evaluations provide an opportunity to access important resources to bolster their case. In this retrospective study, we considered the efficacy of telephonic psychiatric evaluations and assessed their potential as a solution to meet the needs of asylum seekers. Ten affidavits produced from telephonic evaluations were compared to twenty produced from in-person evaluations using a standardized scoring rubric. Providers who conducted telephonic evaluations also completed a structured interview and a qualitative assessment of themes was conducted. Overall, there was a small, but non-significant difference in overall score. The presence of descriptions of cognitive complaints, appearance, motor activity and use of checklists were, however, all significantly lower in telephonic compared to in-person affidavits. Providers agreed that despite limitations, the ability to diagnose and advocate for asylum seekers is equivalent regardless of format. This study identifies that telephonic psychiatric evaluations produce comparable results to in-person evaluations with the benefit of reaching a hard to reach population. Evaluators, lawyers, and judges should consider these results in weighing the risk-benefits of a telephonic evaluation of an asylum seeker.